2020
DOI: 10.1007/s11661-020-05774-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Analysis of Nonaffine Displacements in Disordered Solids Sheared Across the Yielding Point

Abstract: The time evolution and spatial correlations of nonaffine displacements in deformed amorphous solids are investigated using molecular dynamics simulations. The three-dimensional model glass is represented via the binary mixture, which is slowly annealed well below the glass transition temperature and then sheared at a constant strain rate. It is shown that with increasing strain, the typical size of clusters of atoms with large nonaffine displacements increases, and these clusters remain spatially homogeneously… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Therefore, these results demonstrate that the location of the shear band can be predicted at least several periods before the yielding transition. This is in sharp contrast to the shear band formation during the startup deformation, where the strain localization in well-annealed glasses becomes apparent only at the critical strain [14].…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Therefore, these results demonstrate that the location of the shear band can be predicted at least several periods before the yielding transition. This is in sharp contrast to the shear band formation during the startup deformation, where the strain localization in well-annealed glasses becomes apparent only at the critical strain [14].…”
Section: Resultsmentioning
confidence: 61%
“…This definition was first introduced by Falk and Langer and used to identify accurately the location of shear transformations in strained disordered solids [40]. More recently, the spatiotemporal analysis of nonaffine displacements was applied to investigate shear band formation in steadily [12][13][14]42] and periodically [21,23,25,29,30,34] driven amorphous solids, as well as the structural relaxation in thermally cycled [43,44] and elastostatically loaded [45] glasses. Interestingly, the accumulation of atoms with large nonaffine displacements along the xy plane, shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the appearance of clusters of atoms with relatively large nonaffine displacements was connected to rejuvenation of elastostatically loaded binary glasses [18]. In recent years, the collective rearrangements of atoms in disordered solids were also reported during steady [53][54][55][56][57] and periodic [28][29][30][31][32][33][34][35][39][40][41]43,45] deformation and thermal cycling [58][59][60].…”
Section: Resultsmentioning
confidence: 99%
“…While during startup continuous shear deformation of well annealed glasses, the position of strain localization cannot be determined until the yielding strain [34], the location of a 2 shear band during time periodic deformation can be identified at least several cycles before the yielding transition [30]. Furthermore, it was previously demonstrated that mechanical annealing during small-amplitude cyclic shear can be accelerated by periodically alternating shear orientation in two or three spatial dimensions [27].…”
Section: Introductionmentioning
confidence: 99%